Environmental and Institutional Impacts of Tidal River Management: A Case Study on Pakhimara Tidal Basin in Southwestern Bangladesh - Md. Tareq Bin Salam; Atika Ibnat Amin; Tonami Afroz; Md. Mahedi Al Masud (Universitas Sebelas Maret, 2021)
People in southwestern Bangladesh have been facing the waterlogging problem and protesting on the impacts for the nature for a long time. In the 1960s, the government introduced polders, embankments and cross dams to overcome the destructive scenario. Due to the failure of government initiatives, the local people of the coastal area cut into the polder so that the sediment deposited within the beel known as Tidal River Management (TRM). Then, TRM was applied several times in different catchments. The study was carried out from December 2018 to November 2019 to assess the positive and negative environmental and institutional impacts of TRM on Pakhimara beel in Tala Upazila (Sub-district), Satkhira District, by using the Sustainability Index of Tidal River Management (SITRM) framework. Sustainability Indices of TRM were designed to provide information on social, environmental and institutional gains. The environmental and institutional impacts were assessed by conducting household survey and Key Informant Interviews (KIIs). Agricultural impacts on crop, poultry, fisheries and vegetation, were also analyzed by comparing GIS map and agricultural production data (before and after TRM). This study investigated that Pakhimara beel was freed from waterlogging during the with-TRM event by 3,200 ha and the reduction of waterlogging increased agricultural land by 1,500 ha in 2018, compared to 2014. This study argued that only 54% of marginal farmers received crop compensation whereas 85% of crop production decreased due to TRM. For promoting sustainable TRM in the studied area, compensation should be guaranteed for all impacted parties, especially marginal farmers and the creation of employment opportunities, and settlement should be ensured.